Molecular insights into Wnt3a and Wnt5a gene expression in venous insufficiency - Ageed, Fatima Eltayb M.; Tifow, Fadumo Ali; Ibrahim, Leylo Abdullahi; Ismael, Aya B.; Balcioglu, Ozlem; Ozcem, Barcin; Ergoren, Mahmut cerkez (Springer, 2024)
Background Chronic venous insufficiency (CVI) manifests as morphological and functional abnormalities in the venous system, primarily affecting the lower extremities and presenting as leg heaviness, oedema, and varicose veins. CVI is a common vascular disorder characterised by impaired blood flow in the veins, often leading to various clinical manifestations. To better understand the additional underlying mechanisms of CVI, it is essential to explore the role of Wnt proteins, which play a crucial role in regulating signalling processes. This study aimed to investigate the expression levels of the Wnt3a and Wnt5a genes using real-time PCR in patients with venous insufficiency compared to acontrol group. Methods and results 68 participants were included, comprising 29 controls and 39 patients with venous insufficiency from Near East University Hospital. Real-time PCR was utilised for gene expression analysis on a segment of the great saphenous vein biopsy, encompassing all vascular layers, from each participant in both groups. With a significance threshold of p < 0.05, the analysis revealed a significant difference in Wnt3a gene expression (p (=) 0.0007) and a nonsignificant difference in Wnt5a expression levels (p (=) 0.5726) between patients with venous insufficiency and the healthy control group. Conclusion This study indicates fluctuations in the Wnt genes in varicose vein biopsies compared to healthy veins. Consequently, further research is essential to elucidate whether the dysregulation of the Wnt pathway induces venous insufficiency or vice versa. This may facilitate targeted interventions addressing its fundamental molecular aberrations.
Keywords: Venous insufficiency; Varicose veins; wnt3a; wnt5a; Gene expression